Proceedings of the Web Conference 2020 2020
DOI: 10.1145/3366423.3380274
|View full text |Cite
|
Sign up to set email alerts
|

Discovering Strategic Behaviors for Collaborative Content-Production in Social Networks

Abstract: Some social networks provide explicit mechanisms to allocate social rewards such as reputation based on users' actions, while the mechanism is more opaque in other networks. Nonetheless, there are always individuals who obtain greater rewards and reputation than their peers. An intuitive yet important question to ask is whether these successful users employ strategic behaviors to become influential. It might appear that the influencers "have gamed the system. " However, it remains difficult to conclude the rat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 52 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…For example, researchers publish their works in certain venues just because they published their previous works there, and they rarely consider publishing new papers in unfamiliar venues. Xiao et al [22] found that influential researchers employed strategic behaviors when selecting publication venues. However, it is difficult, especially for inexperienced researchers, to select appropriate venues.…”
Section: Introductionmentioning
confidence: 99%
“…For example, researchers publish their works in certain venues just because they published their previous works there, and they rarely consider publishing new papers in unfamiliar venues. Xiao et al [22] found that influential researchers employed strategic behaviors when selecting publication venues. However, it is difficult, especially for inexperienced researchers, to select appropriate venues.…”
Section: Introductionmentioning
confidence: 99%